Estetyka, erotyka i parytet płciowy: Historia piękna i Historia brzydoty pod redakcją Umberta Eco - Obremski, Krzysztof (Wydawnictwo Naukowe UAM w Poznaniu, 2012)
The topic of comparative analysis which is presented in this article is The Story of Beauty and The Story of Ugliness edited by Umberto Eco. Even the covers of these books show the contrast between men and women. How esthetic values build a feedback with sexual parity? Ugly men look at beautiful women – this patriarchal discrimination can’t be cancelled either by the parity of sex in The Story of Beauty, nor men who twice outnumber them in The Story of Ugliness. Also as the unfair sex they are prior sex: they humiliate themselves and elevate women
Esthetics, eroticism and sex parity: Umberto Eco’s History of Beauty and History of Ugliness